Formulation of Suppositories of Alum Produced from Bauxite Waste in Ghana for the Treatment of Hemorrhoid - Daniel A. Bartels; Raphael Johnson; Marcel T. Bayor; George K. Ainooson; Paul P. S. Ossei; Rashid K. Etuaful; Richard Buamah (The Scientific World Journal)
The study sought to formulate and evaluate suppositories using a locally produced brand of alum (Aw) obtained from bauxite waste generated at Awaso bauxite mine in the Western-North region of Ghana, for use in the treatment of hemorrhoids. The suppositories were formulated using shea butter modified, respectively, with amounts of beeswax and theobroma oil. In another development, theobroma oil was modified with different concentrations of beeswax. Drug-base interactions were investigated using attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopy. The suppositories were prepared using the hot melt and trituration methods. Quality control checks were carried out on the formulations. The evaluated parameters included physical characteristics (texture, presence or absence of entrapped air, and contraction holes), weight uniformity, disintegration time, drug content, and in vitro release profile of the alum from the formulated suppositories. An in vivo analysis was carried out on the most suitable formulation to ascertain its efficacy on inflamed tissues using croton oil-induced rectal inflammation in a rat model. A critical examination of the ATR-FTIR spectra revealed no drug-base interactions. The suppository formulations passed all Pharmacopoeia stated tests. The in vivo study revealed the use of suppositories ameliorated the croton oil-induced hemorrhoid in the rectoanal region of the rats.